White Matter Tract Alterations in Drug-Naïve Parkinson’s Disease Patients With Impulse Control Disorders - Mojtahed Zadeh, Mahtab; Ashraf-Ganjouei, Amir; Ghazi Sherbaf, Farzaneh; Haghshomar, Maryam; Aarabi, Mohammad Hadi (Frontiers in Neurology, 2018)
Impulse control disorders (ICDs) are relatively frequent in patients with Parkinson’s disease (PD), although it is still unclear whether an underlying pathological process plays a significant role in the development of ICD in PD apart from dopaminergic replacement therapy. In this study, we have investigated alterations of white matter tract in drug-naïve PD patients with impulse control disorders via diffusion MRI connectometry. Our results showed disrupted connectivity in the complex network of dynamic connections between cerebellum, basal ganglia, cortex and its spinal projections serves as the underlying neuropathology of ICD in PD not interfered with the contribution of dopaminergic replacement therapy. These findings provide the first evidence on involved white matter tracts in the neuropathogenesis of ICD in drug-naïve PD population, supporting the hypothesis that neural disturbances intrinsic to PD may confer an increased risk for ICDs. Future studies are needed to validate the attribution of the impaired corticocerebellar network to impulsivity in PD.